Effect of electrolyte medium on the tensile strength of coconut coir–epoxy composites via liquid plasma treatment - Sudirman, Sudirman; Nurdin, Muh Firdan; Waluyo, Marhadi Budi; Wulandari, Eva Tri; Lebang, Denal (Jurnal Polimesin, 2026)
The application of coconut coir in polymer composites is often restricted by poor interfacial adhesion due to the fiber’s hydrophilic nature. This study investigates the enhancement of tensile strength in coconut coir–epoxy composites via microwave-induced liquid plasma treatment with an electrolyte medium. The experiment employed a randomized design with four fiber treatment groups: untreated (control), plasma-treated in distilled water, plasma-treated in 10% NaCl, and plasma-treated in 10% NaOH. The plasma process was conducted at 400 W for 5 minutes under vacuum conditions (60–70 cmHg). Tensile test results indicate that the electrolyte medium significantly influences the treatment effectiveness. Plasma treatment in a 10% NaOH medium achieved the highest average tensile strength (5.70 MPa), corresponding to a 9.2% improvement over untreated fibers. In contrast, plasma treatment in distilled water resulted in a 21.6% reduction in tensile strength (4.08 MPa). The observed enhancement in the alkaline medium is likely related to combined chemical and physical effects induced by the plasma environment, which may contribute to improved fiber–matrix mechanical interlocking. These findings demonstrate that selecting a conductive, alkaline electrolyte medium is critical for optimizing liquid plasma treatment of natural fibers for composite applications.